PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN (Studi Empiris Pada Perusahaan Non Keuangan Terdaftar di BEI Tahun 2015) - Erin Yuliza Anugrah; Herry Laksito (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to analyze the effect of audit committee effectiveness on financial reporting lead time which is a proxy of the timeliness of reporting. The proxies used for audit committee effectiveness in this study are audit committee independence, audit committee expertise, audit committee size, audit committee meeting frequency, and gender audit committee differences.This research uses 235 number of sample of non-financial companies listed on Indonesia Stock Exchange in 2015. The data used in this research is secondary data that contains data about the date of publication of company's financial report on BEI website and company annual report which is listed on BEI 2015. Sample selection procedure using purposive sampling method and using multiple linear regression analysis as data analysis technique in this research.The result of statistical test shows the audit committee's skill, audit committee size, audit committee meeting frequency, and gender audit committee difference negatively significant to financial reporting lead time, while audit committee independence has no effect on financial reporting lead time.